IMPLEMENTATION OF THE COURSE “NEW PEDAGOGICAL TECHNOLOGIES ”AS A FACTOR OF INCREASE PROFESSIONALISM OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
The problem of the improvement of the content of the future teacher’s training is given in this article. The experiment of teaching o f the course “New pedagogical technologies” is given there.
Keywords: 1